“Non-Markovian” and “directional” errors inhibit scientific self-correction and can lead fields of study astray: an illustration using gardening and obesity-related outcomes - Jon Agley; Sarah E. Deemer; David B. Allison (BMC Medical Research Methodology)
Abstract Herein we coin the terms non-Markovian error and biased Markovian error to describe categories of scientific errors for which general progress within a field of study may be unlikely to result in scientific self-correction. We provide examples of such errors and show their impact on studies about gardening and obesity.